2010
DOI: 10.1039/c0mb00103a
|View full text |Cite
|
Sign up to set email alerts
|

Network based analysis of hepatitis C virus Core and NS4B protein interactions

Abstract: Hepatitis C virus (HCV) is a major cause of chronic liver disease worldwide. Here we attempt to further our understanding of the biological context of protein interactions in HCV pathogenesis, by investigating interactions between HCV proteins Core and NS4B and human host proteins. Using the yeast two-hybrid (Y2H) membrane protein system, eleven human host proteins interacting with Core and 45 interacting with NS4B were identified, most of which are novel. These interactions were used to infer overall protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
74
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 94 publications
1
74
0
Order By: Relevance
“…HCV NS4B was reported to interact with nearly all HCV proteins (30)(31)(32)(33)(34)(35)(36). Therefore, we investigated whether the NS4B inhibitors or their drug-resistant mutations interrupt the interaction of NS4B with other viral proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCV NS4B was reported to interact with nearly all HCV proteins (30)(31)(32)(33)(34)(35)(36). Therefore, we investigated whether the NS4B inhibitors or their drug-resistant mutations interrupt the interaction of NS4B with other viral proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of the GTPase or RNAbinding activity leads to impairment of HCV replication. NS4B has also been reported to interact with many HCV proteins (30)(31)(32)(33)(34)(35)(36), as well as with several cellular proteins (28,37,38). NS4B has been suggested to regulate viral protein translation (39)(40)(41).…”
mentioning
confidence: 99%
“…We also found that cellular proteins associated with energy metabolism, including glycolytic enzymes ENO1, and key regulatory enzymes involved in amino acid transport and metabolism, such as AST and GLS, were disordered. ENO1 is involved in inflammatory responses, cell differentiation [49], viral replication and tumor progression [50,51]. Viral replication requires the coordinated production.…”
Section: The Cellular Physiology and Pcv2 Infectionmentioning
confidence: 99%
“…Thus, unraveling the hostvirus interactome is essential for novel antiviral target identification and for a better understanding of the cellular and viral biology. The majority of previous studies were done using a yeast two-hybrid system (16,17). However, this system is not optimal for membrane-bound proteins like those of HCV.…”
mentioning
confidence: 99%